Semantic Orientation, Syntactic Position and Pragmatic Function of Modifier in Chinese-English Translation - Liu, Huawen (Meta, 2009)
AbstractIn Chinese-English translation the equivalents for noun or verb modifiers are more than often subject to redeployment in the target language. According to the principle that a modifier is supposed to be syntactically located in the immediacy of the modified toward which it is semantically oriented, the displacement of a modifier from where it should be syntactically located is incurred because of pragmatic motivations. However, in the context of Chinese-English translation, the modified can exert more drawing force on the modifier. As a result, the originally displaced modifier, now in a position identical to that of its English equivalent, returns to the modified, the noun or the verb, toward which it is semantically oriented. Or the modifier will resume the syntactic position as close to its modified noun or verb as possible. A conclusive analysis claims that the drawing gravity from the modified in C-E translation results from the translator’s heightened semantic concerns, although some pragmatic effects can be produced as expected or unexpected.